Combination of external fixation using digital six-axis fixator and internal fixation to treat severe complex knee deformity - Shu-guang Liu; Deng-jie Yu; Hui Li; Michael Opoku; Jun Li; Bao-gang Zhang; Yu-sheng Li; Feng Qiao (Journal of Orthopaedic Surgery and Research, 2023)
Abstract Background Severe knee valgus/varus or complex multiplanar deformities are common in clinic. If not corrected in time, cartilage wear will be aggravated and initiate the osteoarthritis due to lower limb malalignment. Internal fixation is unable to correct severe complex deformities, especially when combined with lower limb discrepancy (LLD). Based on the self-designed digital six-axis external fixator Q spatial fixator (QSF), which can correct complex multiplanar deformities without changing structures, accuracy of correction can be improved significantly. Methods This retrospective study included 24 patients who suffered from complex knee deformity with LLD treated by QSF and internal fixation at our institution from January 2018 to February 2021. All patients had a closing wedge distal femoral osteotomy with internal fixation for immediate correction and high tibia osteotomy with QSF fixation for postoperative progressive correction. Data of correction prescriptions were computed by software from postoperative CT scans. Results Mean discrepancy length of operative side was 2.39 ± 1.04 cm (range 0.9–4.4 cm) preoperatively. The mean difference of lower limb was 0.32 ± 0.13 cm (range 0.11–0.58 cm) postoperatively. The length of limb correction had significant difference (p < 0.05). The mean MAD and HKA decreased significantly (p < 0.05), and the mean MPTA and LDFA increased significantly (p < 0.05). There were significant increase (p < 0.05) in the AKSS-O, AKSS-F and Tegner Activity Score. The lower limb alignment was corrected (p < 0.05). The mean time of removing external fixator was 112.8 ± 17.9 days (range 83–147 days). Conclusions Complex knee deformity with LLD can be treated by six-axis external fixator with internal fixation without total knee arthroplasty. Lower limb malalignment and discrepancy can be corrected precisely and effectively by this approach.